Corporate Governance Characteristics and Environmental, Social & Governance (ESG) Performance: Evidence from the Banking Sector of Pakistan - Samina Rooh; Muhammad Zahid; Muhammad Farooq Malik; Muhammad Tahir (Journal of Business & Tourism, 2021)
The purpose of the paper is to examine the impact of corporate governance on environmental, social, and governance (ESG) performance.This paper alsoinvestigates the influence of corporate governance on environmental, social, and governance (ESG) disclosure.The majority of previous empirical research studies have either centered on ESG disclosure in developed economies, but the present problem concerning the corporate sector is defining the role of corporate governance in improving ESG performance inthe banking sectors of Pakistan.This paper is based on quantitative and secondary data approaches. The datawas collected fromthe annual reportsof 17 public and privatecommercial banks of Pakistan through an adapted ESG index. This study applied the Stata 13.0 panel data approach to analyzing the effect of corporate governance on ESG performance. Theresults showed that gender diversity, board independence,and return on assets(ROA) positively affect ESG performance. The board size and firm size havean insignificant impact on the ESG performance. Furthermore, firm age and previous year ESG practices (lag of ESG) have a significant positive role in the improvement of ESG performance.However, in contrast, firm leverage has a negative significant effect on the ESG practices of the banking sectors.This papertries to fulfill the gap by examiningcorporate governance and ESG performance in the banking sectors ofPakistan. The findings of the study have significant implications for the top management of the banks, financial experts, regulatory bodies, investment advisors, academics practitioners, and Pakistan stock exchange towards the better implementation of corporate goverance and ESG practices.